A CMAC-PID based on pitch angle controller for direct drive permanent magnet synchronous wind turbine. (April 2016) - Chen, Diyi; Xu, Peng; Zhou, Rui; Ma, Xiaoyi
The efficiency of wind power conversions systems can be greatly improved using an appropriate control algorithm. This paper deals with a cerebellar model articulation controller coupling with a proportional-integral-derivative controller for a direct drive permanent magnet synchronous wind turbine generator. First, the aerodynamic characteristics of the wind turbine have been studied in detail. Moreover, the transfer function from pitch angle to the speed of the wind turbine is established. Finally, some tests on the proposed method are carried out including random wind speed using numerical simulation. From these tests, several operating conditions are simulated, and satisfactory results are obtained.